Memorandum of understanding between Universiti Teknologi MARA and Dar El Hadith El Hassania Institution, Al Quaraouiyine University, Morocco / Akademi Pengajian Bahasa - Universiti Teknologi MARA, Akademi Pengajian Bahasa (Universiti Teknologi MARA (UiTM), 2020)
In order to strengthen the relationship between UiTM and Dar El Hadith El Hassania Institution and reinforce international cooperation in academic, scientific and research aspects.